Blood pressure variables and cardiovascular risk: New findings from advance - Kengne, A.; Czernichow, S.; Huxley, Rachel; Grobbee, D.; Woodward, M.; Neal, B.; Zoungas, S.; Cooper, M.; Glasziou, P.; Hamet, P.; Harrap, S.; Mancia, G.; et al. (American Heart Association, 2009)
The relative importance of various blood pressure indices on cardiovascular risk in people with type 2 diabetes mellitus has not been established. This study compares the strengths of the associations between different baseline blood pressure variables (systolic blood pressure [SBP], diastolic blood pressure [DBP], pulse pressure [PP], and mean arterial pressure) and the 4.3-year risk of major cardiovascular events in the Action in Diabetes and Vascular Disease: Preterax and Diamicron-Modified Release Controlled Evaluation Study. Mean (SD) age for the 11 140 participants was 65.8 years (6.4 years). During follow-up, 1000 major cardiovascular events, 559 major coronary events, and 468 cardiovascular deaths were recorded. After adjustment for age, sex, and treatment allocation, the hazard ratios (95% CIs) associated with 1 increment in SD for the risk of major cardiovascular events were 1.17 (1.10 to 1.24) for SBP; 1.20 (1.13 to 1.28) for PP; 1.12 (1.05 to 1.19) for mean arterial pressure; and 1.04 (0.98 to 1.11) for DBP. The areas under the receiver operating characteristic curve were slightly higher for SBP and PP compared with mean arterial pressure and DBP for major cardiovascular and coronary events. Using achieved instead of baseline blood pressure values marginally improved the effect estimates for SBP, DBP, and mean arterial pressure, with no significant differences in the areas under the receiver operating characteristic curve between models with SBP and those with PP. In conclusion, SBP and PP are the 2 best and DBP is the least effective determinant of the risk of major cardiovascular outcomes in the relatively old patients with type 2 diabetes mellitus participating in the Action in Diabetes and Vascular Disease: Preterax and Diamicron-Modified Release Controlled Evaluation Study. However, SBP may be the simplest and most useful predictor across a wider range of age groups and populations. © 2009 American Heart Association, Inc.